EKSPERYMENTALNE TERAPIE – DEFINICJE I REGULACJE - Galewicz, Włodzimierz (Diametros, 2023)
The subject of this article are the definitional and regulatory aspects of experimental (or innovative) therapies, understood either as new and unproven treatment methods that can be tested – and for this purpose used – also in clinical trials, or as applications of these new and unproven procedures in medical practice. After a short introduction, recalling one of the important sources of the concept of experimental or innovative therapy, which was the Belmont Report, I first discuss the problems related to the definition of experimental therapy (as a new and nonvalidated medical procedure used to improve the patient's health), and then the controversial issues related to its regulation (including in particular the required control to which each such therapeutic intervention should be subject). Finally, I point out the importance of the discussions on experimental therapy reported in this article, conducted in other countries or in international contacts, for the necessary revision or reinterpretation of Polish regulations regarding therapeutic experiments.